Architecture 3.0 : the disruptive design practice handbook - Moser, Cliff (London : Routledge, 2014)
'This book provides a definitive guide for the future direction of the practice and profession of architecture. This comprehensive and practical handbook is a timely response to the reality that the traditional architectural profession is dead. The old model of fee for labor, based on the development of documents for construction has been failing for years and its demise is now complete with the Great Recession. Which forces us to now reconsider our world.....what type of profession and practice will replace the old model? Focusing on the concept of disruption, the book provides a set of ideas and tools in order to create a new sustainable practice. But what is disruption? A disruption is a process, product, or service that disrupts an existing market or existing market solution. Combined with innovation, disruption improves a product or service in ways that the market is not expecting or prepared for. The disruptive innovative solution provides a completely different business approach to the market, that isn't just about lowering fees or pursuing a different set of clients, but the provision of a new and different client solution. In five parts, Cliff Moser provides you with all the tools and know-how to implement changes that will serve you and your practice in the short, medium and long term. Written at a crucial time for the industry, this is essential reading for every architect'--
Includes bibliographical references and index.
Keywords: Architectural practice; Architectural services marketing